The computer quantum chemical modeling of basic magnesium carbonate stabilized by biopolymers - A. V. Blinov; A. A. Gvozdenko; A. B. Golik; M. A. Kolodkin; M. A. Pirogov (Современная наука и инновации)
As part of this work, computer quantum chemical modeling of the stabilization of basic magnesium carbonate by biopolymer molecules: hydroxyethylcellulose, methylcellulose, chitosan and hyaluronic acid was carried out. The simulation was carried out by combining the basic magnesium carbonate and biopolymer through a magnesium atom and various functional groups, respectively. As a result of the analysis of data obtained during computer quantum chemical modeling, it was found that the stabilization of basic magnesium carbonate by biopolymers is energetically advantageous (∆E > 736 kcal/mol) and chemically stable (0.034 ≤ η ≤ 0.075 eV). The optimal configuration of the interaction of the basic magnesium carbonate with each biopolymer has also been determined. As a result, it was found that the stabilization of the basic magnesium carbonate by chitosan, in which the interaction occurs through a hydroxyl group attached to the C3 of the glucosamine residue, has optimal values of the difference in energy (∆E = 736.224 kcal/mol) and chemical hardness (η = 0.059 eV) compared with other biopolymers.